Philosophical perspectives on emotional intelligence, self efficacy and job satisfaction among secondary school teachers - Hassan, Aminuddin; Kham, Fong Pheng; Sim, Kuan Yew (Center for Promoting Ideas (CPI), USA, 2013)
It is important to observe the components of teaching and how teachers themselves perform in the philosophical perspective for a deeper and more thorough analysis. A teacher’s occupation is considered stressful because they need to carry out multifaceted tasks in order to achieve given educational goals while establishing good relationship with others related in the teaching profession. Prior studies have found out that teacher self-efficacy can assess the multifaceted tasks in teaching profession because it reflects one’s capability to perform the variety tasks in teaching and it drives one to attain the particular goal. Moreover, teachers with emotional intelligence enable them to establish satisfactory relationship with others because they are aware of their emotion and are less likely to lose control when they interact with others. Previous studies indicated that being a secondary school teacher is a stressful profession and many have left the teaching profession due to dissatisfaction. Therefore, there is a need to study the effect of teachers’ emotional intelligence and self-efficacy on job satisfaction among secondary school teachers.